Test of the Effectiveness of Bioherbicide of Reed Extract (Imperata Cylindrica) on Weed Control on Corn Plants (Zea Mays L) Rainbow Cultivar - Arfan Sidik, Muchamad; Nur Ayuni, Anis; Dukat, Dukat; Deden, Deden (Jurnal Agrosci, 2024)
Corn is one of the strategic food crops in Indonesia. The decline in corn production can be influenced by various factors, including OPT disturbances, such as weeds. The presence of weeds on cultivated land can reduce the yield of 20-80% of cultivated crops. The presence of weeds can also be a host for pests and diseases. The rampant use of chemical herbicides has become a concern in the agricultural sector; with the negative impact caused by the use of chemical herbicides, there have been various efforts to suppress the use of chemical herbicides and switch to bioherbicides or organic herbicides that are environmentally friendly. The study aimed to determine the ability of reed extract bioherbicides to control weeds in maize plants, the most effective concentration to control weeds in maize plants, and phytotoxicity in maize plants. The experimental method used Group Random Design (RAK), 8 treatments were repeated 4 times, so that 32 experimental plot units were obtained, namely A1 (Control), A2 (20%), A3 (25%), A4 (30%), A5 (35%), A6 (40%), A7 (45%), A8 (50%). The results showed that the bioherbicide of reed extract did not have a real effect on all vegetative observations of corn plants and weed populations, weed biomass, and weed competitiveness value and did not cause phytotoxicity in corn plants. Bioherbicides have a significant effect on the yield of dried maize. The bioherbicide concentration of 50% reed extract produced 3.72 kg of dried pipilan corn or equivalent to 9.3 tons/ha